KEPEMIMPINAN MILLENIAL DAN DAMPAKNYA TERHADAP TRANSFORMASI SOSIAL DESA: (Analisis Strukturasi Kemunculan Kepemimpinan Milenial di Kalurahan Guwosari, Kapanewon Pajangan, Kabupaten Bantul) - Aminah Aminah; Fatih Gama Abisono Nasution (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
This research examines millennial leadership and its impact on village social transformation. This research departs from the phenomenon of many youths returning to the village to seize political leadership in the village. This phenomenon is commonly found in the Special Region of Yogyakarta, but not many have researched it. Previous studies looked at the phenomenon go-politics, usually in political parties, social movements, and business organizations, but this study looks at go-politics youth in the village realm. In particular, the research aims to explore what factors shape the structural conditions for the birth of millennial leadership for social transformation. This research is a qualitative type with the method used is an exploratory study in accordance with the objectives of this study. Taking the location in Guwosari Village, Bantul Regency, with the argument that the lurah officials are from the millennial generation and their leadership involves youth as the main target of change. Collecting data using observation, direct and virtual interviews, and documentation techniques. By using a structuration theoretical framework, the results of the study show that the conditions that enable millennial leadership are born because people are thirsty for change and want leaders with new and fresh faces; and the will of the millennial generation to become leaders. This is because in the previous period, Guwosari was led by a lurah with an elderly background as well as a religious figure. The millennial leadership in Guwosari also has an impact on encouraging the process of social transformation. Institutionally, currently the Guwosari Village is still undergoing a process of transformation (becoming). So that the ongoing social transformation is still vulnerable to shifting if it is not institutionalized. In this case, the institutionalization from leader to government is a challenge for millennial leaders.